(untitled) (Research, Society and Development, 2025)
Hyperinsulinemic Hypoglycemia of Infancy (HHI) is the leading cause of persistent hypoglycemia in neonates and children, with an estimated incidence of 1 case per 50,000 live births. Its prevalence is higher among boys, neonates, and infants. This article aims to understand the characteristics, diagnostic methods, and recommended treatment of this condition. To this end, the methodology included the case report of an 8-month-old male patient with seizures and apparent neuropsychomotor developmental delay followed by difficult-to-control hypoglycemia. Throughout his hospitalization, repeated episodes of hypoglycemia persisted, leading to a diagnosis of congenital hyperinsulinism. Ultimately, the child’s condition improved after administration of diazoxide, resulting in hospital discharge with continued outpatient follow-up. It is therefore concluded that this is a clinical condition that is difficult to diagnose and that, if not addressed in time, can lead to permanent damage to the patient, especially of a neuropsychomotor nature.Therefore, it is essential that its approach is effective and timely.